Comparison of Sensitivity to Fusarium Head Blight in Soft Red and Hard Red Winter Wheat Varieties - G. Sassenrath; K. Andersen Onofre; J. Lingenfelser; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2022)
Fusarium head blight (scab) is a problem for wheat production in high rainfall areas. This is a report of research examining the response of wheat varieties on disease susceptibility and wheat yield and quality. Hard red wheat varieties had more disease than the soft red wheat varieties in 2021. Wheat yield was correlated with disease severity.
Keywords: wheat; fungicide; Fusarium Head Blight; fungal disease; soil microbial activity